Association of Blood Pressure, Its Treatment, and Treatment Efficacy With Volume of White Matter Hyperintensities in the Population-Based 1000BRAINS Study. Issue 5 (November 2021) - Gronewold, Janine; Jokisch, Martha; Schramm, Sara; Jockwitz, Christiane; Miller, Tatiana; Lehmann, Nils; Moebus, Susanne; Jöckel, Karl-Heinz; Erbel, Raimund; Caspers, Svenja; Hermann, Dirk M.
Abstract : White matter hyperintensities (WMHs) of presumed vascular origin are a frequent finding in cerebral magnetic resonance imaging of older people. They are attributed to small vessel disease and involved in the pathogenesis of cognitive decline. Since vascular risk factors, especially arterial hypertension, predispose to small vessel disease, we analyzed the association of systolic blood pressure (SBP), diastolic blood pressure (DBP), and antihypertensive medications with WMH volume in 560 participants of the 1000BRAINS study, drawn from the population-based Heinz Nixdorf Recall study (65.2±7.5 years; 51.4% men). Further, we analyzed treatment efficacy using a classification of 6 BP treatment groups defined by antihypertensive medication and level of BP: (1) untreated BP <120/<80 mm Hg, (2) untreated SBP 120 to 139 or DBP 80 to 89 mm Hg, (3) untreated BP ≥140 or ≥90 mm Hg, (4) treated BP <120/<80 mm Hg, (5) treated SBP 120 to 139 or DBP 80 to 89 mm Hg, and (6) treated BP ≥140 or ≥90 mm Hg. Median WMH volume (Q1–Q3) was 4.6 (3.0–7.8) cm 3 ; mean±SD of SBP and DBP was 128.6±17.4 and 76.1±9.8 mm Hg. In multivariable linear regression models, continuous SBP (β=0.63 cm 3 per 10 mm Hg [95% CI, 0.32–0.94]), DBP (0.64 cm 3 per 5 mmHg [95% CI, 0.37–0.91]), and antihypertensive treatment (1.23 cm 3 [95% CI, 0.14–2.23]) were significantly associated with WMH volume. Regarding treatment efficacy, only participants with hypertension despite treatment (treated BP ≥140 or ≥90 mm Hg) had significantly increased WMH volume (4.24 cm 3 [2.36–6.13]) compared with normotension without treatment (untreated BP <120/<80 mm Hg). Our results suggest that WMHs represent a marker of advanced hypertension pathology. Hence, early treatment should prevent WMHs. Abstract : Supplemental Digital Content is available in the text.